Fixation of proximal humerus fracture in adult by locking plate: Clinical study - Dr. Vivek Amritbhai Patel; Dr. Vishal A. Pushkarna; Dr. Dhruvin J. Patel (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Aim: The present study aimed to examine the functional outcome of the locking plate in the proximal humerus fracture treatment. Material and Methods: The study consists of 20 patients diagnosed with NEER’s 2 – part, 3- part, and 4 – part proximal humerus fracture. All the included patients were treated with internal locking plates. Based on the functional evaluation by Constant-Murley shoulder score and the assessment of radiological union foundation. Results: Excellent results were obtained in 45% of the patients, a good result was seen in 25%, 20% of the patients had fair results and the poor result was seen in 10% of the patients. The mean Constant-Murley shoulder score that was obtained in the present study was 75.04. Conclusion: It’s concluded that there is a satisfactory functional outcome with the fixation of the proximal humerus fracture with locking plates. While using the plate fixation for fracture the plate position is of the utmost importance. Due to angular stability, the locking plates are the advantageous implants in case of proximal humeral fracture.